The Influence Of The Arabic Short Speech Program On Improving The Language Skills of Students/ أثر تطبيق برنامج إلقاء الكلمات العربية في تنمية المهارات اللغوية لدى طلاب المرحلة الجامعية - Uril Bahruddin; Bisri Mustofa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research stems from the problem of the difficulty of mastering language skills for foreign-speaking Arabic learners. This study aims to answer two questions: How is the application of the Arabic short speech program for Ar-Raya University students in Sukabumi, Indonesia? What is the program's impact on the development of their language skills? This study uses descriptive methods. Qualitative data were collected through interviews and observations. The results of this study are (1) the purpose of the short speech program is to familiarize students with public speaking, organized by a special team, carried out through the written preparation stage, delivering a speech for a maximum of 5 minutes without looking at the text. (2) this program has a good impact on students because it can improve their ability in Arabic, enrich their vocabulary, and familiarize them with speaking Arabic, using vocabulary in sentences, and choosing the correct method. The findings show that the Arabic short speech program can be used as a medium to improve Arabic language skills.